Application of The Elaboration Likelihood Models in The Political Campaign of Sudrajat-Syaikhu During The West Java Regional General Election in 2018 - Andhika Kurniawan Pontoh; Farrah Mardiati Soeharno; Mutia Adia Risjad (Journal of Politics and Policy, 2019)
The Regional Election (PILKADA) of West Java in 2018 has seen significant change in the increasing electability of one of the governor and vice governor candidates Sudrajat-Ahmad Syaikhu ahead of the election day. Amid the estimation commissioned by various survey institutions, the final results of the vote count showed a significant jump in the vote collection of Sudrajat-Syaikhu. These significant jumps can be achieved because the candidate utilized campaign persuasion messages by emphasizing religious values, supporting for certain groups social and political causes and was benefited by the existing authorities both from the government and the party. Government programs that should be prioritized, were promoted on the shades of significant phenomenal issues to get voters’ attention. This article tries to explain the application of the Elaboration Likelihood Model to the Sudrajat-Syaikhu's campaign that succeeded in changing voter behavior in West Java. The Elaboration Likelihood Model asserts two main channels for conveying persuasion messages, the central route and the peripheral route. In the Elaboration Likelihood Model theory, persuasive messages will be received differently by the recipient. This is because recipients have differences in motivation and ability to comprehend the conveyed messages. Central persuasion messages can be seen in the form of messages containing strong logical and directed information, whereas peripheral persuasion messages comprise short-cut elements related to authority, commitment to the group, reciprocal relationships, scarcity and social proof. This paper will describe the application of the Elaboration Likelihood Model theory in the Sudrajat-Syaikhu campaign strategy which utilized and was benefited from the peripheral route using Islamic populist strategies, support for #2019GantiPresiden cause and 212 movement, and authorities from party, military and the ruling government. The utilization of this peripheral route is proven able to increase the number of votes in the end, which reflects the reality of prioritization of religious values above other aspects in West Java.Key words: Elaboration Likelihood Model, Voters Motivation, Pilgub Jabar 2018, Sudrajat-Syaikhu